Pendampingan Penguatan Literasi Digital di SD Muhammadiyah Program Khusus Baturan dan SD Muhammadiyah Plus Malangjiwan - Laili Etika Rahmawati; Harun Joko Prayitno; Agus Budi Wahyudi; Dini Restiyanti Pratiwi; Dipa Nugraha; Melati Beauty; Eko Purnomo; Tiara Surya Madani; Laily Rahmatika; Desy Anggraini; Riyani Eka Arnumasari; Dhimas Arsyad Arrajiv; Winda Dwi Lestari (Warta LPM, 2022)
Digital literacy must be instilled as early as possible, starting at least formally from elementary schools (SD). However, digital literacy learning in elementary schools has not been implemented effectively. Some schools still encounter obstacles, one of which is caused by the limitation and availability of digital literacy devices or media in schools. This obstacle was also experienced by the Muhammadiyah Special Program Elementary School of Baturan and the Muhammadiyah Plus Elementary School Malangjiwan. Basic digital literacy skills, such as using a common word processor like Microsoft Word, have not been fully mastered by students, whilst these skills are very important for them to master in this digital era. This community service was carried out by providing direct assistance to students to use Microsoft Word. The stages in this activity were starting from observation, pre-test, to post-test in using Microsoft Word. The hands-on mentoring method allowed students to learn to recognize and use Microsoft Word. This community service shows that there has been an increase in students’ competence in understanding Microsoft Word through the given activities, students have real experience to use word processor, and students' digital literacy improve. It is expected that in the future, students who already have the initial ability to use word processor from the results of this community service program, will improve their skills more and the school can support it by continuing this kind of activity through a digital literacy enhancement program.